The story of Disney : 100 years of wonder - Baxter, John, 1939-; Steele, Bruce C. (Disney Editions, 2023)
"The Walt Disney Company honors its 100th anniversary in 2023. As part of the festivities, this must-have coffee table book showcases the company's history and rich legacy--past, present, and future--through vibrant voices and rare Disney concept art and photographs"--